Money laundering and tax evasion : Do international measures have a significant impact in sub-Saharan Africa? - Dirk Kohnert (Zenodo, 2024)
Sub-Saharan Africa (SSA) accounts for a third of the countries on the Financial Action Task Force (FATF) grey list. In the Money Laundering and Terrorist Financing (ML/TF) Ranking and Risk Assessment Tool, the region performed poorly in terms of resilience to ML/TF, with more than 60% of countries falling into the high-risk category. Although countries on the grey list are not subject to sanctions, inclusion on the list has a significant impact on their economies. This includes a significant reduction in capital inflows and foreign direct investment. The four main sources of illicit financial flows from SSA, South Africa, the Democratic Republic of Congo, Ethiopia and Nigeria, accounted for more than 50% of total illicit financial flows. While SSA received nearly 2 trillion in foreign direct investment (FDI) and official development assistance (ODA) between 1980 and 2018, it issued over 1 trillion in illicit financial flows. These illicitly acquired funds and diverted from the region continue to pose a development challenge. Illicit financial flows increased overall, but not concerning trade. In the 38 years from 1980 to 2018, they increased significantly in the 2000s, in parallel with the growth of African trade. Emerging and developing countries in Asia and the Middle East have become key targets. Previous initiatives to curb money laundering and improve the exchange of tax information between countries have largely failed, including the three most important: the Financial Action Task Force (founded in 1998), the Global Forum on Transparency and Exchange of Information for Tax Purposes (founded in 2009) and the Inclusive Framework on Base Erosion and Profit Shifting (founded in 2016). First, African countries lack the resources and capacity to address illicit financial flows. Second, many advanced economies are not sufficiently engaged in these initiatives. However, the repatriation of illegal funds is an important tool for strengthening the resource base of African countries. In 2020, for example, the United States and the self-governing British Crown Dependency of Jersey, one of the world's most notorious tax and money laundering havens, reached an agreement with Nigeria to repatriate more than 300 million stolen by Nigeria's former military dictator General Sani Abacha. – – Subsahara-Afrika (SSA) macht ein Drittel der Länder auf der grauen Liste der Financial Action Task Force (FATF) aus. Im Ranking und Risikobewertungstool für Geldwäsche und Terrorismusfinanzierung (ML/TF) schnitt die Region in Bezug auf die Widerstandsfähigkeit gegenüber ML/TF schlecht ab, wobei mehr als 60 % der Länder in die Hochrisikokategorie fielen. Obwohl Länder auf der grauen Liste keinen Sanktionen unterliegen, hat die Aufnahme in die Liste erhebliche Auswirkungen auf ihre Wirtschaft. Dazu gehört eine deutliche Reduzierung der Kapitalzuflüsse und ausländischen Direktinvestitionen. Auf die vier Hauptquellen illegaler Finanzströme aus SSA, Südafrika, die Demokratische Republik Kongo, Äthiopien und Nigeria, entfielen mehr als 50 % der gesamten illegalen Finanzströme. Während SSA zwischen 1980 und 2018 fast 2 Billionen US-Dollar an ausländischen Direktinvestitionen (FDI) und offizieller Entwicklungshilfe (ODA) erhielt, emittierte es über 1 Billion US-Dollar an illegalen Finanzströmen. Diese unrechtmäßig erworbenen und aus der Region abgeleiteten Gelder stellen weiterhin eine Entwicklungsherausforderung dar. Die illegalen Finanzströme nahmen insgesamt zwar zu, nicht jedoch im Verhältnis zum Handel. In den 38 Jahren von 1980 bis 2018 stiegen sie in den 2000er Jahren deutlich an, parallel zum Wachstum des afrikanischen Handels. Schwellen- und Entwicklungsländer in Asien und im Nahen Osten sind zu Hauptzielen geworden. Die bisherigen Initiativen zur Eindämmung der Geldwäsche und zur Verbesserung des Austauschs von Steuerinformationen zwischen Ländern sind weitgehend gescheitert, darunter die drei wichtigsten: die Financial Action Task Force (gegründet 1998), das Global Forum on Transparency and Exchange of Information for Tax Purposes (gegründet 2009) und das Inclusive Framework on Base Erosion and Profit Shifting (gegründet 2016). Erstens mangelt es den afrikanischen Ländern an Ressourcen und Kapazitäten, um gegen illegale Finanzströme vorzugehen. Zweitens engagieren sich viele fortgeschrittene Volkswirtschaften nicht ausreichend in diesen Initiativen. Allerdings ist die Rückführung illegaler Gelder ein wichtiges Instrument zur Stärkung der Ressourcenbasis afrikanischer Länder. Im Jahr 2020 einigten sich beispielsweise die Vereinigten Staaten und das selbstverwaltete britische Krongebiet Jersey, eines der berüchtigtsten Steuer- und Geldwäscheparadiese der Welt, mit Nigeria auf die Rückführung von mehr als 300 Millionen US-Dollar, die vom ehemaligen nigerianischen Militärdiktator General Sani Abacha gestohlen worden waren.
Keywords: D23; D25; D53; D63; D74; E21; F35; G28; O17; Z13; 330; Money laundering; Embezzlement; Corruption; tax evasion; Terrorism financing; Informal economy; Sub-Saharan Africa